THE ROLE OF CUSTOMS AUTHORITIES AND CUSTOMS CLEARANCE PROCEDURES IN THE FORMATION OF SECURITY IN THE MARKET OF PERFUMERY AND COSMETIC PRODUCTS - PELYK, Lesya; SAPOZHNYK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
One of the main tasks facing the customs authorities in ensuring the economic security of the State is: replenishment of the State budget revenues in full in accordance with the State Customs Service’s planned task, which is the fiscal function of the customs authorities; protection of the national producer and the domestic market from unfair foreign competition; customs control, especially in terms of movement of goods, with a view to detecting the facts of illegal import/export and smuggling. The article presents the results of the study of the role of customs authorities and the customs clearance procedures carried out by them in the course of their professional activities in the formation of security in the market of perfumery and cosmetic products. It is shown that despite the changing geopolitical, economic and trade situation on the world stage, customs and law enforcement authorities should constantly carry out effective work to detect and suppress crimes that may harm the economic security of Ukraine. The issue of safety of perfume and cosmetic products is also relevant in terms of harm to consumer health, as the safety of these products depends on the composition, quality of the initial components, technological process of production, storage and sale conditions, and consumption conditions. At each stage of the life cycle, physical and chemical processes may occur in the FCP that cause changes that are hazardous to human health. Therefore, to verify the safety of products (in particular, cosmetics), a set of various tests is carried out. Accordingly, the issue of the role and functions of customs authorities in ensuring the safety of perfumes and cosmetics is becoming more relevant in order to increase the efficiency of control over the customs value of certain goods imported into the customs territory of Ukraine and to ensure a uniform approach when deciding on their customs value. It is concluded that customs authorities are state institutions with a high potential for developing equipment in ensuring the economic security of the country, striving for constant mutual exchange of experience and for improving professional qualifications